Inflammatory Disorders - Pokorski, Mieczyslaw (Advances in Experimental Medicine and Biology, 2015)
The mechanistic basis of chronic inflammation remains unclear. The research sheds new light on the immune cells expressing the activation markers HLA-DR and regulatory T cells (Tregs) and the cells expressing Siglec receptors as being key players in the immune system responsiveness to antigens and thus in lung tissue damage of chronic inflammation. The results help understand the mechanisms of action of common drugs used in COPD, such as formoterol, tiotropium, or corticosteroids, and point to novel drug targets. The chapters also deal with brain damaging effects, by far unrecognized, of inhaled corticosteroid therapy, a time-proven management of chronic inflammatory airway conditions; asthma being a case in point. Novel methods, likely less producing side effects, of macrolide antibiotics administration by inhalation are discussed, emphasizing not only bacteriostatic but also anti-inflammatory action.